1982
DOI: 10.1107/s0567740882006293
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the zwitterion inosine cyclic 3',5'-monophosphate (cIMP) monohydrate. Analysis of torsional flexibility in the furano–phosphate moiety

Abstract: Inosine cyclic 3',5'-monophosphate (clMP), which has been implicated in hormonal and regulatory control mechanisms, crystallizes with one water molecule of hydration (C 10HI1NaO7P. H20) in the monoclinic space group P2~ (Z = 2) with unit-cell constants a --6.190 (3), b = 13.090 (2), c = 9.095 (2) A and fl = 108.43 (2)°; do = 1.656, d c = 1.654 g cm -3. The structure was solved by the multisolution technique and refined by the least-squares method to a final R of 0.034 using 1422 intensities. The free acid of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…An extremely short N−H···O (P) hydrogen bond is revealed in the structure of 3 [Figure , Table ]. The N···O distance is much shorter than that in Emsley's compound [C 6 H 11 N 3 H 2 ] + [H 2 PO 4 ] - [N···O 2.611, 2.661 Å]. 4a, An examination of the structures available in the Cambridge database showed that the N(−H)···O (P) distance in 3 is at the lower end for such hydrogen bonds (cf. Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…An extremely short N−H···O (P) hydrogen bond is revealed in the structure of 3 [Figure , Table ]. The N···O distance is much shorter than that in Emsley's compound [C 6 H 11 N 3 H 2 ] + [H 2 PO 4 ] - [N···O 2.611, 2.661 Å]. 4a, An examination of the structures available in the Cambridge database showed that the N(−H)···O (P) distance in 3 is at the lower end for such hydrogen bonds (cf. Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…For derivatives [15][16][17][18][19] with substituent Y trans (3, Z = 0, Y = substituent), 1,3-syn axial repulsions resulting from the axial P=0 should be very similar to those in the diesters themselves. Here, stereoelectronic interactions must account for the measured differences in geometries ( , ', bond angles) and bond lengths compared to the diesters.…”
Section: Introductionmentioning
confidence: 99%
“…Since the interest of this paper is in the conformations of the phosphate and ribose rings of nucleoside cyclic 3',5'-monophosphates and derivatives thereof, we have not complied available information on the conformations of the nucleobases with regard to C(l')-N rotation, i.e., the glycosyl torsion angle. Comparisons of glycosyl torsion angles for the diesters (1,2, 5-9) of Table I can be found in refs 15 and 17. Glycosyl torsion angles for [10][11][12][13][14][15][16][17][18][19] show no evident systematic correlation with phosphorus configuration. The related question of the nature of intramolecular interactions in the solid state, which can involve H bonding between nucleobases and also nucleobase-phosphate oxyanion interactions, has not been addressed.…”
Section: Introductionmentioning
confidence: 99%